Analysis of Budget Planning Performance Values at the State Christian Institute of Tarutung as a Benchmark for Budget Management - Hely Joisen; Binur Panjaitan (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study analyzes the Budget Planning Performance Score of Institut Agama Kristen Negeri (IAKN) Tarutung as a benchmark for budget management. The analysis uses Monitoring & Evaluation (Monev) data from the Ministry of Finance up to November 2025 and supporting literature. The overall Planning Performance Score is 50.50/100, composed of Output Detail Achievement (CRO) 56.27%, Use of Output Cost Standards (SBK Usage) 83.33%, and SBK Efficiency 0.00%. Key issues identified are: (1) several Outputs (RO) not fully realized, reducing RVRO; (2) blocked budget items that prevent full RVRO reporting; (3) mismatches among budget realization, RVRO achievement, and SBK efficiency calculations possibly due to data inaccuracies in the Monev application. Recommendations include accelerating budget realization, resolving or removing budget blocks, coordinating data verification with the Directorate General, updating Monev/system data, and strengthening internal monitoring and evaluation to improve planning efficiency and budget performance.